2002
DOI: 10.1016/s1010-7940(01)01122-8
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for Mycobacterium avium complex lung disease in the clarithromycin era

Abstract: Although it is associated with relatively high morbidity, surgery provides a high sputum conversion rate for patients whose MAC disease responds poorly to drug therapy. Even in the present clarithromycin era, pulmonary resection remains the treatment of choice when MAC lung disease has not been successfully eradicated by drug treatment alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
2
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 15 publications
2
34
2
2
Order By: Relevance
“…Results of surgery vary; however, in the macrolide era, morbidity and mortality have generally decreased compared to those associated with premacrolide surgeries (349,350). In the premacrolide era, Corpe (82) reported a 7% perioperative mortality rate with a rate of significant postoperative complications of 18% for the surviving patients from a series of 131 patients before macrolides were available.…”
Section: Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Results of surgery vary; however, in the macrolide era, morbidity and mortality have generally decreased compared to those associated with premacrolide surgeries (349,350). In the premacrolide era, Corpe (82) reported a 7% perioperative mortality rate with a rate of significant postoperative complications of 18% for the surviving patients from a series of 131 patients before macrolides were available.…”
Section: Surgerymentioning
confidence: 99%
“…Shiraishi et al (349,350) also indicated that 94% of 33 patients who underwent pulmonary resection in Japan were sputum culture negative following surgery. Those authors did, however, note two late deaths: one patient died of unknown causes 12 years after the surgery, and another died of respiratory failure 2 years postoperatively.…”
Section: Surgerymentioning
confidence: 99%
“…According to several reports of the recurrence rate of nontuberculous mycobacterial infection after surgery, the sputum negative conversion rate was high, at 82%-94%. 10,[19][20][21] It is commonly believed that the treatment duration includes 12 months of sputum culture negativity while on therapy, 22) and, in the present case, the patient continued to receive oral antibiotic therapy after surgery, and has been followed up carefully. Regarding surgery for M. chelonae, much is unknown, including the long-term prognosis and chemotherapy to prevent recurrence.…”
Section: )mentioning
confidence: 71%
“…[8][9][10] Since surgical treatment for the M. avium complex infection is generally effective in controlling infection, therefore, it is likely that surgical treatment for M. chelonae infection is also effective. 10,12,[19][20][21] Surgery may be useful in the following settings: i) patients with localized disease, ii) patients, in whom medical therapy is ineffective, and iii) patients who cannot tolerate medical therapy. 2,12) Pulmonary resection should be considered before the expansion of lesions in patients in whom complete resection is considered possible based on the number and extent of lesions.…”
Section: )mentioning
confidence: 99%
“…Pulmonary resection for Mycobacterium avium lung disease continues to play an important role when the disease has not been successfully treated by chemotherapy alone (1). However, the indication and the timing of pulmonary resection are still problematic, and to date there are no adequate recommendations.…”
Section: Introductionmentioning
confidence: 99%